Analisis Manajemen Risiko Pembiayaan Mudharabah pada Perbankan Syariah (Bank Muamalat) - Nufus, Shoufa Hyatun; Wigati, Sri (Jurnal Serambi Ekonomi dan Bisnis, 2024)
Risk management of mudharabah financing at Bank Muamalat is an effort to minimize the risks that occur, both at the pre-contract and post-contract stages. The research method used was descriptive qualitative and a case study at Bank Muamalat Indonesia Medan Branch. In this research, researchers use the collected data to become systematic, orderly, structured and meaningful data. Risk management in mudharabah financing at Bank Muamalat is an effort to minimize the risks that occur, both at the pre-contract and post-contract stages. Pre-agreement mitigation is carried out by complying with the Standard Operational Procedures set internally by the bank, selecting mudharib candidates, and analyzing the business feasibility of mudharib candidates. Meanwhile, post-contract mitigation is carried out by complying with the provisions set by Bank Indonesia to avoid various risks that exist in sharia banking. This research emphasizes one of the financing products in sharia banks, namely mudharabah financing, and shows that risk management of mudharabah financing really needs to be done to maintain the sustainability of sharia banks. This is because the financing risk that occurs can disrupt the operational activities of Islamic banks in their function as lending institutions. The increase in financing risk at Bank Muamalat Indonesia can be caused by increased financing, which can disrupt the stability of sharia banks and result in losses if not managed properly